Comparing downpayment and interest rate mortgage subsidies: an analytical approach - Bebczuk, Ricardo Néstor (2014)
Our paper sets up a simple model to assess, to the best of our knowledge for the first time, the relative pros and cons of housing downpayment and interest rate subsidies on the access to and the stability of the mortgage market. Our analysis unveils a number of relevant policy lessons for the design of housing subsidy programs, namely: (a) Under fiscal neutrality (same government outlay), both subsidies have the same positive effect on the ability and willingness to repay. But, for such neutrality to hold, the percentage interest rate subsidy must be larger than the downpayment subsidy, which is rare to happen in practice; (b) The interest rate subsidy raises the loan size a bank is willing to grant, but the downpayment subsidy does not, the reason being that the latter actually diminishes the need for bank financing for a given property value; (c) When targeting lower income households, the downpayment subsidy is superior to the interest rate subsidy, as the former increases the loan-to-value and debt-to-income ratios, two key criteria for mortgage borrower eligibility. By the same token, the downpayment subsidy is more likely to have a stronger effect on low and medium value housing units; (d) Such progressivity comes at the cost of a higher probability of default, meaning that some trade-off between equity and financial stability may emerge; (e) Subsidies are likely to put upward pressure on housing prices. The downpayment subsidy has a direct effect (by injecting fiscal resources to cover part of the property price) and an indirect effect (by easing the access to the mortgage market); (f) The interest rate subsidy only has the latter effect; and (g) Compared to the interest rate subsidy, the downpayment support promotes a less aggressive competition in the real estate market.